If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 3y = 5b + -4y Solving 2b + 3y = 5b + -4y Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. 2b + -5b + 3y = 5b + -5b + -4y Combine like terms: 2b + -5b = -3b -3b + 3y = 5b + -5b + -4y Combine like terms: 5b + -5b = 0 -3b + 3y = 0 + -4y -3b + 3y = -4y Add '-3y' to each side of the equation. -3b + 3y + -3y = -4y + -3y Combine like terms: 3y + -3y = 0 -3b + 0 = -4y + -3y -3b = -4y + -3y Combine like terms: -4y + -3y = -7y -3b = -7y Divide each side by '-3'. b = 2.333333333y Simplifying b = 2.333333333y
| (2x^2+8x)+(5x^2-3x)= | | 12+0.08=x | | 14000000+0.1x=x | | d=45-3P | | 13500+0.1x=x | | n/2≤10 | | X-0.1x=13500000 | | 5x-4y+18=0 | | -8r-3s=177 | | 20x^3+24x^2-30x+2=0 | | y=-3x/4=5 | | 30n+22=929 | | 4-1/3+2i= | | 2-3(3X-10)=8 | | 2x+3.0=x+3.3 | | [(m^3+m)+(m^2+1)][(m^3+m)-(m^2+1)]= | | 29+p+20= | | 5x-1.2=2x-03 | | 5x^2-5y^2=7 | | 6r+7s=223 | | c=-8+8+(-10) | | x^5-13x^3+42x=0 | | -3z-10=2z+5 | | 18/100=x/200 | | 8p+2p+9p-5= | | 18/100=70/x | | V/82 | | 7x(2y)= | | 102/3m | | t=b+6 | | 3m/102 | | 16x^2+180x=0 |